Youth in Action: Exploring Emerging Forms of Civic Engagement and Digital Philanthropy among Millennial and Generation Z Muslims - Faizah, Nur; Manalundong, Shahid (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2026)
The proliferation of digital technology presents unique opportunities and challenges for the civic and philanthropic engagement of Muslim Millennials and Generation Z. This study aims to map the emerging forms of their digital participation, with a focus on the negotiation between the logic of digital platforms and Islamic socio-religious values. Employing a qualitative library research method, this paper systematically analyzes scholarly literature to explore how religious principles such as ukhuwah (solidarity) and ummah (community) are adapted within digital spaces. Findings indicate that Muslim youth are not passive consumers of technology; rather, they actively create hybrid practices, such as #SedekahOnline campaigns, faith-based crowdfunding, and virtual volunteering, that integrate digital efficiency with spiritual obligations like zakat and sadaqah. Religious values serve as a key motivator for digital philanthropy. However, challenges remain, including limited digital literacy, the commodification of religion, and infrastructural inequality. The study concludes that fostering meaningful digital participation requires social engineering that interconnects technology, critical digital education, and Islamic ethics. By centering cultural-religious dimensions in the analysis, this research addresses a gap in existing literature and provides a more contextualized understanding of youth engagement in the digital age.